1980
DOI: 10.1038/285078a0
|View full text |Cite
|
Sign up to set email alerts
|

Mutations which alter the function of the signal sequence of the maltose binding protein of Escherichia coli

Abstract: The maltose binding protein of Escherichia coli is secreted into the external periplasmic compartment of the cell by virtue of an amino-terminal signal sequence. Using DNA sequencing, we have determined the precise nature of mutations in the signal sequence which prevent the export of the maltose binding protein, causing it to accumulate in the cytoplasm in its precursor form. In most cases, the change of a single hydrophobic or uncharged amino acid to a charged amino acid within the signal sequence is suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(115 citation statements)
references
References 25 publications
1
114
0
Order By: Relevance
“…MalE is exported into the bacterial periplasmic space by means of an N-terminal signal sequence which has a length of 26 residues and is cleaved during the export process. Mutations in the signal sequence can prevent MalE export and provoke its accumulation within the cytoplasm [5]. MalE is a protein binding maltose and maltodextrins which is necessary for the transport of these sugars across the bacterial envelope (reviewed in [I]).…”
Section: Production Inmentioning
confidence: 99%
“…MalE is exported into the bacterial periplasmic space by means of an N-terminal signal sequence which has a length of 26 residues and is cleaved during the export process. Mutations in the signal sequence can prevent MalE export and provoke its accumulation within the cytoplasm [5]. MalE is a protein binding maltose and maltodextrins which is necessary for the transport of these sugars across the bacterial envelope (reviewed in [I]).…”
Section: Production Inmentioning
confidence: 99%
“…Direct evidence for a role of these segments in the translocation process has been provided by genetic experiments showing that mutations affecting specific residues within the signals prevent passage of the polypeptides across the membrane (6) . In fact, DNA sequence analysis of mutant genes for altered polypeptides ofthe maltose binding protein of E. coli (9), which cannot be transferred to the periplasmic space, and for defective polypeptides of the lambda receptor protein (53), which do not reach the outer membrane and remain within the cytoplasm, has shown that all these mutations involved either substitutions in the signal sequence, from a single hydrophobic or uncharged amino acid to a charged one, or small deletions within the hydrophobic portion of the signals .…”
Section: Role Of Cotranslational Insertion Signals In Determining Thementioning
confidence: 99%
“…These signals share some common features (von Heijne, 1983): They are basic at the N-terminus, apolar in the middle, and have small, uncharged amino acid residues preceding the site of cleavage by the signal (or leader) peptidase. Genetic studies (Emr et al, 1978;Bassford & Beckwith, 1979;Bedouelle et al, 1980;Emr & Silhavy, 1980) have revealed that the integrity of the hydrophobic stretch of signal peptides is vital for protein transport across the membrane barrier.…”
mentioning
confidence: 99%